Identification of Citrullinated Hsp90 Isoforms as Novel Autoantigens in Rheumatoid Arthritis–Associated Interstitial Lung Disease1. Issue 4 (28th March 2013) - Harlow, Lisa; Rosas, Ivan O.; Gochuico, Bernadette R.; Mikuls, Ted R.; Dellaripa, Paul F.; Oddis, Chester V.; Ascherman, Dana P.
Abstract Objective Subsets of patients with rheumatoid arthritis (RA) develop extraarticular complications that include interstitial lung disease (ILD). Because standardized algorithms for identification of RA patients at risk of developing clinically significant ILD are lacking, the purpose of this study was to elucidate unique serologic markers of RA‐associated ILD (RA‐ILD). Methods Sera from RA patients with ILD and from RA patients without ILD were used to immunoprecipitate citrullinated and uncitrullinated proteins derived from K562 cell extracts. Mass spectrometry was performed to facilitate identification of citrullinated proteins differentially immunoprecipitated by RA‐ILD patient sera. These candidate proteins were then used as substrate antigens in custom enzyme‐linked immunosorbent assays (ELISAs) for high‐throughput screening of sera obtained from cohorts of patients with RA, RA‐ILD mixed connective tissue disease (MCTD), or idiopathic pulmonary fibrosis (IPF). Results Differential immunoprecipitation and subsequent mass spectrometric sequencing identified citrullinated Hsp90α and citrullinated Hsp90β as candidate autoantigens in patients with RA‐ILD. ELISAs incorporating uncitrullinated and citrullinated isoforms of Hsp90 as substrate antigens demonstrated that sera from patients with RA‐ILD preferentially recognized citrullinated versions of Hsp90 with moderate sensitivity (range 20–30%) and great specificity (>95%) relative to sera derived from patients with RA alone (without ILD), patients with MCTD, or patients with IPF. Conclusion These studies demonstrate the utility of a novel autoantigen discovery method based on differential immunoprecipitation of citrullinated protein extracts. Application of these techniques identified citrullinated versions of Hsp90α and Hsp90β as autoantibody targets distinguishing RA‐ILD from RA without ILD, MCTD, and IPF, suggesting that anti–citrullinated Hsp90α/β autoantibodies may serve as effective biomarkers for the potentially devastating pulmonary manifestations of RA‐ILD.